2018
DOI: 10.1177/0956797617736887
|View full text |Cite
|
Sign up to set email alerts
|

Female Chess Players Outperform Expectations When Playing Men

Abstract: "Stereotype threat" has been offered as a potential explanation of differential performance between men and women in some cognitive domains. Questions remain about the reliability and generality of the phenomenon. Previous studies have found that stereotype threat is activated in female chess players when they are matched against male players. I use data from over 5.5 million games of international tournament chess and find no evidence of a stereotype threat effect. In fact women players outperform expectation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 43 publications
0
14
0
Order By: Relevance
“…As for stereotype threat, a recent slew of studies has failed to find evidence that situations likely to induce threat do in fact hamper females’ performance in maths or other cognitive domains. The studies in question include several meta-analyses (Flore & Wicherts, 2015; Stoet & Geary, 2012), a number of large, pre-registered replications (Finnigan & Corker, 2016; Flore et al., 2019) and an analysis of 5.5 million chess games played in international tournaments, which found that women’s performance was better, rather than worse, under conditions of stereotype threat (Stafford, 2018; although see Smerdon et al., 2020). Meanwhile, on the other side of the ledger, a recent study failed to replicate the finding that stereotype threat impairs men’s performance on tests of language ability (Chaffee et al., 2020).…”
Section: Sex Differences In Cognitive Aptitudesmentioning
confidence: 99%
“…As for stereotype threat, a recent slew of studies has failed to find evidence that situations likely to induce threat do in fact hamper females’ performance in maths or other cognitive domains. The studies in question include several meta-analyses (Flore & Wicherts, 2015; Stoet & Geary, 2012), a number of large, pre-registered replications (Finnigan & Corker, 2016; Flore et al., 2019) and an analysis of 5.5 million chess games played in international tournaments, which found that women’s performance was better, rather than worse, under conditions of stereotype threat (Stafford, 2018; although see Smerdon et al., 2020). Meanwhile, on the other side of the ledger, a recent study failed to replicate the finding that stereotype threat impairs men’s performance on tests of language ability (Chaffee et al., 2020).…”
Section: Sex Differences In Cognitive Aptitudesmentioning
confidence: 99%
“…As for stereotype threat, a recent slew of studies has failed to find evidence that situations likely to induce threat do in fact hamper females' performance in math or other cognitive domains. The studies in question include several meta-analyses (Flore & Wicherts, 2015;Stoet & Geary, 2012), a number of large, pre-registered replications (Finnigan & Corker, 2016;Flore et al, 2019), and an analysis of 5.5 million chess games played in international tournaments, which found that women's performance was better, rather than worse, under conditions of stereotype threat (Stafford, 2018). Meanwhile, on the other side of the ledger, a recent study failed to replicate the finding that stereotype threat impairs men's performance on tests of language ability (Chaffee et al, 2019).…”
Section: The Nature and Nurture Of Sex Differences In Cognitive Aptitmentioning
confidence: 99%
“…Supporting this criticism, Stafford (2018) found that skilled female chess players show a reverse stereotype-threat effect when they play against men in tournaments, performing slightly better than would be expected on the basis of their Elo ratings (see the following paragraph). Although this reverse stereotype-threat effect is very small, it suggests that underperformance by members of stereotyped groups might not emerge in high-stakes real-world contexts.…”
mentioning
confidence: 90%
“…In the top half of each panel, black dots are point estimates, and gray bars indicate 95% confidence intervals. Panel (a) shows results using the sample of female players (as in Stafford, 2018); in contrast, panel (b) shows results using a sample of male players matched to female players on the basis of age, Elo rating, and their differences to obtain a placebo sample of male players that was younger and lower rated on average than the total pool of male players. The arrow in (a) indicates where we replicated Stafford’s reverse stereotype-threat effect.…”
mentioning
confidence: 99%